Perubahan Tradisi Pembacaan Al-Barzanji ke Surat Yasin dalam Masyarakat Bugis - Nur Persada; Mugiyono Mugiyono; Muhammad Arpah Nurhayat (Program Studi Ilmu Al quran dan Tafsir, Fakultas Ushuluddin dan Pemikiran Islam, Universitas Islam Negeri Raden Fatah Palembang, 2020)
The background in this research is that in the past the reading of Yasin letters in Bugis society was very rare. However, the reading of Al-Barzanji is very often read in various events, for example the hajj pilgrimage, which every Friday night always reads Al-Barzaji, housewarming events, housewarming thanksgiving and other celebration events. Surah Yasin is read only at death events. The Bugis community also understands that reading the Yasin letter is read by someone who has died, more than that there are some of the Bugis people who understand that reading the Yasin letter means praying for someone to die soon. Over time the reading of Al-Barzanji began to be shifted with the reading of the Yasin letter which was previously read for people who have passed away now has been read at events such as moving houses, thanksgiving wedding, thanksgiving for hajj and other celebratory events. There is also a change in understanding of the reading of the Yasin letter which is now understood to ask for salvation to Allah SWT. The purpose of reading the Yasin letter in the Bugis community in Sungai Semut Village, Makarti Jaya Subdistrict, Banyuasin Regency, is as safety, to get the pleasure of Allah SWT, to facilitate death and to make matters easier. The researcher uses the study of the living Qur'an, which is a scientific study in the Al-Quran that looks at social phenomena in the form of the Al-Quran that lives in the Muslim community.